Культовые памятники и сакральные объекты бесермян - Попова Елена Васильевна (УИИЯЛ УрО РАН, 2011)
Экземпляры: КР (20120514) / Инвентарный номер: 1087055 / Цена: / Сис.шифр: 63.5 / Авт.знак: П 58 / ГРНТИ: 03 / ББК: 63.521(=664)